Migration of the Temporal RDB into Temporal ORDB including - Mohamed, Bahaj (Transactions on Engineering and Computing Sciences, 2017)
This paper proposes an approach for migrating existing relational database (TRDB) according to SQL: 2011 standard into temporal object relational database (TORDB) including Bitemporal data. This is done with methods that can extract various functions from a TRDB, which is based on the different kind of the relationships between tables. To do that we’re going to enhance a representation of a varying time database’s structure in order to make hidden semantic explicit. In contrast to other studies, our main goal here is to offer a first and better solution to mentioned limits to existing works, in order to provide the efficient method for the translation from TRDB to TORDB. We are going to take an existing RDB with bitemporal data features as input, we provide our meta-model in order to get a correct description of a data structure, enriches its metadata representation, and generates a bitemporal data Model (BTDM), which captures essential characteristics of temporal databases for migration. A prototype has been developed which proves the effectiveness of this solution, and temporal queries has been made with help of Oracle 12C.